DRUGS & SOCIETY - Grant, Judith (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
An important social problem facing our society today is that of drug use/abuse. This problem cuts across all cultures, as well as, across social class, gender, and racial groups. It affects the economy of the country, as well as, the image we, as a nation, project to other peoples. It is a political issue of not just national, but also international proportions. In order to understand this problem better, this course attempts to place "drugs" in a sociological perspective by using the sociological imagination. The objectives of this course:1. Develop an awareness of the historical precedents & social implications of drug use/abuse.2. Understand the relevant terms & definitions within the field.3. Develop an understanding of how drugs influence us psychologically, physiologically, & socially.4. Develop an awareness of the social, legal, moral, & ethical issues surrounding drug use/abuse.5. Understand the factors in play in relation to social policy in various governmental and community institutions.